Youth development in football : lessons from the world's best academies - Nesti, Mark. 1959-; Sulley, Chris (New York : Routledge, 2015)
"The identification and development of talented young players has become a central concern of football clubs at all levels of the professional game, as well as for national and international governing bodies. This is the first book to offer a comprehensive survey and assessment of youth development programmes in football around the world, to highlight best practice, and to offer clear recommendations for improvement. The book draws on original, in-depth research at eight elite professional football clubs, including Barcelona, Ajax and Bayern Munich, as well as the French national football academy at Clairefontaine. It adopts a multi-disciplinary approach, including psychology, coaching and management studies, and covers every key topic from organisational structures, talent recruitment and performance analysis to player education and welfare. Written by two authors with extensive experience in English professional football, including five Premiership clubs, this book is important reading for any student, researcher, coach, administrator or academy director with an interest in football, youth sport, sports development, sports coaching or sport management"--
Includes bibliographical references and index.
Keywords: Soccer players -- Training of -- Cross-cultural studies; Soccer players -- Recruiting -- Cross-cultural studies; Soccer teams -- Cross-cultural studies; SPORTS & RECREATION / General; SPORTS & RECREATION / Soccer; SPORTS & RECREATION / Coaching / Soccer